The management of miniature horses at pasture in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (without specialisation) at Massey University, Manawatū campus, New Zealand - Goh, Sheen Yee (Massey University, 2020)
Studies on the demographics, feeding management and health care practices of Miniature horses in New Zealand have yet to be conducted. Thus, the aim of this study is to describe the demographics, feeding management and health care practices of Miniature horses in New Zealand. To achieve the aim of this study, an online survey was conducted using the Qualtrics Survey Software. There were 232 valid responses from respondents who kept 1,183 Miniature horses, representing approximately one third of the New Zealand Miniature horse population. Miniature horses were kept for leisure and companionship (56%), competition (35%) and for breeding (7%). The median number of Miniature horses kept by owners for leisure and companionship was significantly lower (two horses) than those kept for competition (six horses) or for breeding (ten horses) (p<0.05). The majority (79%) of Miniature horses were kept at pasture on low (<1,000 kg DM/ha) to moderate (~2,000 kg DM/ha) pasture masses across seasons. Pasture access was more commonly restricted by respondents during spring (60%), summer (60%), and autumn (55%) than in winter (43%). The majority (n=173/198, 87%) of respondents practiced pasture-restriction strategies such as strip grazing (n=118), temporary use of a paddock with little grass (n=99), confinement for part of a day in a stable or yard (n=94), turning out horses to graze in the early morning only (n=42), or fitting a grazing muzzle (n=24). Another pasture restriction strategy cited by respondents (n=15) was provision of a track system. Respondents indicated the mode daily number of hours of stabling was 7-12 hours (n=57/195, 29%). Miniature horses kept primarily for competition were stocked at a significantly higher stocking density (13 horses/ha) compared with those kept for leisure and companionship (10 horses/ha) or for breeding (12 horses/ha) (p<0.05). The overall median stocking density was 10 horses/ha, (~1,100 kg live weight/ha). Although the stocking density appeared to be high, on a live weight basis, it was comparable to the stocking density of other classes of equine livestock. In addition to feeding on pasture, most owners provided the horses with additional feed (n=194/232, 84%). Additional feedstuffs were hay (n=180), chaff (n=130), premixed concentrates (n=117), fermented forages (n=51), and other types of feed (n=33) such as oats, copra, soy, molasses, and sugar beet pulp. Respondents (n=200/214, 93%) dewormed their Miniature horses between two and four times annually as a routine preventive measure (n=156/199, 78%), and of the respondents who vaccinated their Miniature horses in the last year (n=41/199, 21%), tetanus and strangles vaccines were the most administered vaccine types (n=20/41, 49%).
Keywords: demographics; deworming; miniature horses in New Zealand; pasture feeding; vaccination; 300302 Animal management